2016
DOI: 10.3390/molecules21081069
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Evaluation of the Biological Activities of Essential Oils Derived from the Greek Aromatic Plant Species Ocimum basilicum, Mentha spicata, Pimpinella anisum and Fortunella margarita

Abstract: Natural products, known for their medicinal properties since antiquity, are continuously being studied for their biological properties. In the present study, we analyzed the composition of the volatile preparations of essential oils of the Greek plants Ocimum basilicum (sweet basil), Mentha spicata (spearmint), Pimpinella anisum (anise) and Fortunella margarita (kumquat). GC/MS analyses revealed that the major components in the essential oil fractions, were carvone (85.4%) in spearmint, methyl chavicol (74.9%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 45 publications
(60 reference statements)
7
57
1
4
Order By: Relevance
“…Anise oil's medicinal properties have already been proven and include treatment of non-fatty liver diseases [70]; antidepressant [71], antifungal [72] and antioxidant properties capable of eliminating up to 48% of the free radicals generated in DPPH assay using 48.5 mg/mL [73,74].…”
Section: Pimpinella Anisum Lmentioning
confidence: 99%
“…Anise oil's medicinal properties have already been proven and include treatment of non-fatty liver diseases [70]; antidepressant [71], antifungal [72] and antioxidant properties capable of eliminating up to 48% of the free radicals generated in DPPH assay using 48.5 mg/mL [73,74].…”
Section: Pimpinella Anisum Lmentioning
confidence: 99%
“…Standart olarak Troloks kullanılmıştır. Değerler mmol Troloks eşdeğeri (TE) g kuru ağırlık olarak ifade edilmiştir (mmol TE/g ka) [21].…”
Section: Antioksidan Kapasitesinin Belirlenmesiunclassified
“…*indicates a biomarker designated with "key activity"; the biomarker value for the treated cells was significantly different (p<0.05) from that of the vehicle control at the tested concentration, with an effect size of at least 10% (more than 0.05 log ratio units). MCP-1-Monocyte Chemoattractant Protein 1; VCAM-1 -Vascular Cell Adhesion Molecule 1; ICAM-1 -Intracellular Cell Adhesion Molecule 1; IP-10 -Interferon Gamma-Induced Protein 10; I-TAC -Interferon-inducible T-cell Alpha Chemoattractant; IL-8 -Interleukin 8; MIG -Monokine Induced by Gamma Interferon; EGFR -Epidermal Growth Factor partially attributed to its anti-inflammatory and spasmolytic features recently showed that SEO rich in carvone (85.4%) exhibited antiproliferative activity in cancer cells [1].…”
Section: Bioactivity Profile Of Seo In the Human Dermal Fibroblast Symentioning
confidence: 99%